Medical students' individual and social empathy: A follow-up study. (3rd June 2019) - Wellbery, Caroline; Barjasteh, Tina; Korostyshevskiy, Valeriy
Abstract: Background: The Social Empathy Index (SEI) measures self-reported empathy for individuals and for vulnerable groups. In a previous study, we published first-year medical students' SEI scores before and after completing a course on the social determinants of health. We re-administered the SEI to the original student cohort entering their 4th year. Methods: Survey data were analyzed for individual and social empathy components using repeated measures ANOVA. Associations of demographic data and the latest scores were analyzed using either two sample t -test or ANOVA. Results: Of 130 4th-year eligible medical students, 76 (58%) completed all three surveys. The mean "Affective Mentalizing" score increased by 0.15 points from the first to fourth year of medical school, p < 0.05. A concomitant decline was observed in "Emotional Regulation" decreasing 0.68 points, p < 0.001. "Contextual Understanding of Systemic Barriers" (CU) increased in mean score by 0.26 points, p = 0.006. Discussion: Our findings support promoting interventions to combat a decline of emotional regulation in their clinical years. The consistent increase in CU at each follow-up testing point may indicate a need to focus on students' sense of self-efficacy in addressing the social determinants of health. Social empathy scores might predict which students are likely to choose primary care specialties.